Hubungan Lama Penggunaan Komputer dan Intensitas Pencahayaan dengan Keluhan Kelelahan Mata pada Pekerja di Hotel KC - Antartika, Bianca Arcasiatectura; Amrullah, Afif Amir; Buntara, Arga; Permatasari, Putri (Universitas Ahmad Dahlan, 2019)
1) Background: Interactions between workers and computers create a variety of risks, one of which is complaints of eye fatigue. Lighting intensity is considered a risk factor that can cause complaints of eye fatigue as well. The preliminary study suggests that several workers experienced discomfort in the eye area, neck and back pain, and mild eye irritation. The purpose of this research was to determine the relationship between the duration of computer use and lighting intensity with complaints of eye fatigue. 2) Method: This research is analytical quantitative with a cross-sectional design. In this study, the researcher used a total sampling technique. A total of 43 operators were recruited as samples. The instruments used were questionnaires and a lux meter. A chi-square test was used to analyze the data at 95% confidence level. 3) Result and Conclusion: The results show that the duration of computer use variable was significantly assotciated with complaints of eye fatigue (p 0.004 < α), while lighting intensity variable was not associated with complaints of eye fatigue (p 0.275 > α). 4) Suggestion: Managing the duration of computer use by resting according to the 20-20-20 rule is recommended. The hotel should add, replace, or suistain all existing lights and provide information and education to all operators as well.